Nitrate reductase activity in leaves as a plant physiological indicator of in vivo biological nitrification inhibition by Brachiaria humidicola - Karwat, Hannes; Sparke, Marc-André; Rasche, Frank; Arango, Jacobo; Nuñez, Jonathan; Rao, Idupulapati M.; Moreta, Danilo; Cadisch, Georg (Elsevier, 2019)
The tropical forage grass Brachiaria humidicola (Bh) controls soil microbial nitrification via biological nitrification inhibition (BNI). The aim of our study was to verify if nitrate reductase activity (NRA) in Bh roots or leaves reflects in vivo performance of BNI in soils. NRA was measured in roots and leaves of contrasting accessions and apomictic hybrids of Bh grown under controlled greenhouse and natural field conditions. Nitrate (NO3−) contents were measured in soil solution and in Bh stem sap to validate NRA data. Potential soil nitrification rates (NRs) and leaf δ15N values were used to verify in vivo BNI by the NRA assay in the field study. NRA was detected in Bh leaves rather than roots, regardless of NO3− availability. NRA correlated with NO3− contents in soils and stem sap of contrasting Bh genotypes substantiating its reflectance of in vivo BNI performance. Additionally, leaf NRA data from the field study significantly correlated with simultaneously collected NRs and leaf δ15N data. The leaf NRA assay facilitated a rapid screening of contrasting Bh genotypes for their differences in in vivo performance of BNI under field and greenhouse conditions, but inconsistency of the BNI potential by Bh germplasm was observed. Among Bh genotypes tested, leaf NRA was closely linked with nitrification activity, and consequently with actual BNI performance. It was concluded that NRA in leaves of Bh can serve as an indicator of in vivo BNI activity when complemented with established BNI methodologies (δ15N, NRs) under greenhouse and field conditions.